Erosion Modeling in Overburden Excavation in Mining Areas with the Approach of Rain Intensity and Duration - Rifki Aditya; Sabaruddin Sabaruddin; Budhi Setiawan (Postgraduate, University of Mataram, 2023)
This study investigates erosion modeling in overburden excavation in mining areas with the approach of rain intensity and duration. The main variables considered included rainfall erosion as well as slope length and slope, which were identified as key factors in predicting soil management. The linear regression method evaluated the relationship between independent variables (rainfall erosion, length, and slope) and dependent variables (soil management). The analysis showed that in Model 1, not all independent variables significantly influenced soil management. However, Model 2 revealed that precipitation erosion and slope length and slope significantly affected the dependent variables. These results provide an in-depth understanding of how weather and topographic factors affect soil management practices in mining environments. These findings can be used as a basis for environmental conservation and mitigation decision-making, especially in minimizing soil erosion due to mining activities. By paying attention to these factors, it is hoped that soil management practices can be improved to achieve better environmental sustainability. Further research is recommended to expand this understanding in various geographical conditions and mining environments